2016
DOI: 10.1007/s11357-016-9885-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene-based aggregate SNP associations between candidate AD genes and cognitive decline

Abstract: Single nucleotide polymorphisms (SNPs) in and near ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, complement receptor 1 (CR1), EPHA1, EXOC3L2, FERMT2, HLA cluster (DRB5-DQA), INPP5D, MEF2C, MS4A cluster (MS4A3-MS4A6E), NME8, PICALM, PTK2B, SLC24A4, SORL1, and ZCWPW1 have been associated with Alzheimer's disease (AD) in large meta-analyses. We aimed to determine whether established AD-associated genes are associated with longitudinal cognitive decline by examining aggregate variation across these gene regions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 33 publications
4
48
1
Order By: Relevance
“…Notably, no group differences were observed on common standardized measures of declarative memory (delayed recall of semantic or episodic memories), suggesting that the AG risk genotype is specific to impairing generalization of learning in older adults who are otherwise cognitively healthy on measures of declarative memory. In other studies with nondemented elderly (Andrews, Das, Anstey, & Easteal, ; Andrews, Das, Cherbuin, Anstey, & Easteal, ; Engelman et al, ), as well as, AD patients (Chung et al, ; Nettiksimmons, Tranah, Evans, Yokoyama, & Yaffe, ), ABCA7 risk variants were related to variations in episodic memory using standardized assessments. Our results therefore suggest that the concurrent discrimination and generalization behavioral paradigm may be a useful tool for assessing the mild cognitive deficits seen in the earliest phases of prodromal AD before the more severe and more commonly reported deficits in episodic memory arise later in the course of the disease.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, no group differences were observed on common standardized measures of declarative memory (delayed recall of semantic or episodic memories), suggesting that the AG risk genotype is specific to impairing generalization of learning in older adults who are otherwise cognitively healthy on measures of declarative memory. In other studies with nondemented elderly (Andrews, Das, Anstey, & Easteal, ; Andrews, Das, Cherbuin, Anstey, & Easteal, ; Engelman et al, ), as well as, AD patients (Chung et al, ; Nettiksimmons, Tranah, Evans, Yokoyama, & Yaffe, ), ABCA7 risk variants were related to variations in episodic memory using standardized assessments. Our results therefore suggest that the concurrent discrimination and generalization behavioral paradigm may be a useful tool for assessing the mild cognitive deficits seen in the earliest phases of prodromal AD before the more severe and more commonly reported deficits in episodic memory arise later in the course of the disease.…”
Section: Discussionmentioning
confidence: 85%
“…99 The association of this SNP was replicated in a Chinese cohort, 101 and further work showed that this SNP is associated with cis-gene expression levels of DRB1 in the temporal cortex and cerebellum. 102 Nettiksimmons et al 103 showed an association of the DRB5-DRB1 clusters with cognitive decline at the gene-level, and more recently methylation of DRB5 in the brain was associated with pathological AD, with another peak of association in DRA. 104 Yokoyama et al 105 determined that variants associated with autoimmune disease are also associated with AD and found that a SNP close to DRB5 is associated with AD and psoriasis.…”
Section: Hla and Parkinson's Diseasementioning
confidence: 99%
“…Following up these findings, we recently showed that higher predicted C4 RNA expression was associated with poorer performance on measures of memory function in both patients with SZ and healthy participants, and with reduced cortical activation during visual task performance in healthy participants. 3 This, along with evidence that other risk-related genes and proteins within the complement system are also associated with variation in both cognition and brain structure in both patients and healthy individuals, [4][5][6][7][8][9][10][11][12] led us to consider whether variation within genes that encode the complement system could, as a whole, influence cognition.…”
Section: Introductionmentioning
confidence: 99%